2006
DOI: 10.1091/mbc.e05-08-0709
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Endothelial Nitric-Oxide Synthase Involves a Ternary Complex with Caveolin-1 and NOSTRIN

Abstract: Recently, we characterized a novel endothelial nitric-oxide synthase (eNOS)-interacting protein, NOSTRIN (for eNOStrafficking inducer), which decreases eNOS activity upon overexpression and induces translocation of eNOS away from the plasma membrane. Here, we show that NOSTRIN directly binds to caveolin-1, a well-established inhibitor of eNOS. Because this interaction occurs between the N terminus of caveolin (positions 1-61) and the central domain of NOSTRIN (positions 323-434), it allows for independent bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 57 publications
4
46
0
Order By: Relevance
“…15,16 More recently, the same group showed that NOSTRIN is involved in vascular development and that loss of NOSTRIN resulted in impaired vascular patterning. Here, we showed that in human and rodent glomeruli, NOSTRIN is expressed predominantly in epithelial podocytes and interacts with proteins such as CD2AP that are known to be essential for proper slit-membrane function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 More recently, the same group showed that NOSTRIN is involved in vascular development and that loss of NOSTRIN resulted in impaired vascular patterning. Here, we showed that in human and rodent glomeruli, NOSTRIN is expressed predominantly in epithelial podocytes and interacts with proteins such as CD2AP that are known to be essential for proper slit-membrane function.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been attributed to the control of endothelial nitric oxide synthase activity and has been shown to interact with dynamin-2, neural WiskottAldrich syndrome protein, and caveolin-1. 15,16 More recently, the same group showed that NOSTRIN is involved in vascular development and that loss of NOSTRIN resulted in impaired vascular patterning. 9 Here, we showed that in human and rodent glomeruli, NOSTRIN is expressed predominantly in epithelial podocytes and interacts with proteins such as CD2AP that are known to be essential for proper slit-membrane function.…”
Section: Discussionmentioning
confidence: 99%
“…Two other proteins named as eNOS-interacting protein (NOSIP) and eNOS traffic inducer (NOSTRIN) that specifically modulate the caveolin/eNOS interaction have been described (33,113,165). NOSTRIN also functions as an adaptor protein to recruit dynamin-2, which is a large GTPase and a positive modulator of eNOS (118) to facilitate internalization of eNOS (113).…”
Section: Caveolins and Coexpression Partnersmentioning
confidence: 99%
“…42,43 Previously, factors modulating NOS were studied largely by investigating stimulated NOS activity, NOS activity in vitro and in transfection-modified cells using mainly the citrulline assay. Such activation and the interaction of NOS and its binding partners may be modulated by proteins such as heat shock protein 90 (HSP90), 44 nitric oxide synthase traffic inducer (NOSTRIN), 45 and eNOS interacting protein (NOSIP), 46 as well as kinase action by Akt (protein kinase B, PKB) and PKA (protein kinase A). 47 Basal endothelial nitric oxide production has been difficult to measure and study with the citrulline assay.…”
Section: Effects Of Protein Kinase G Modulator Drugs On Endothelial Imentioning
confidence: 99%